RETRACTED: Assessment of Expression of Regulatory T Cell Differentiation Genes in Autism Spectrum Disorder - Akbari, Mohammadarian; Eghtedarian, Reyhane; Hussen, Bashdar Mahmud; Eslami, Solat; Taheri, Mohammad; Neishabouri, Seyedeh Morvarid; Ghafouri-Fard, Soudeh (Frontiers in Molecular Neuroscience, 2022)
Dysfunction of regulatory T cells (Tregs) has been shown to affect the etiology of autism spectrum disorder (ASD). Differentiation of this group of T cells has been found to be regulated by a group of long non-coding RNAs (lncRNAs). In this study, we have examined the expression of five lncRNAs that regulate this process in the blood samples of ASD cases compared with controls. These lncRNAs were FOXP3 regulating long intergenic non-coding RNA (FLICR), MAF transcriptional regulator RNA (MAFTRR), NEST (IFNG-AS1), RNA component of mitochondrial RNA processing endoribonuclease (RMRP), and Th2 cytokine locus control region (TH2-LCR). Expression of RMRP was significantly lower in total ASD cases compared to controls [expression ratio (95% CI) = 0.11 (0.08–0.18), adjusted P-value < 0.0001]. This pattern was also detected in both men and women cases compared with corresponding controls [expression ratio (95% CI) = 0.15 (0.08–0.29) and 0.08 (0.03–0.2), respectively]. Likewise, expression of NEST was reduced in total cases and cases among men and women compared with corresponding controls [expression ratio (95% CI) = 0.2 (0.14–0.28); 0.22 (0.12–0.37); and 0.19 (0.09–0.43), respectively; adjusted P-value < 0.0001]. Lastly, FLICR was downregulated in total cases and cases among both boys and girls compared with matched controls [expression ratio (95% CI) = 0.1 (0.06–0.19); 0.19 (0.08–0.46); and 0.06 (0.01–0.21), respectively; adjusted P-value < 0.0001]. These three lncRNAs had appropriate diagnostic power for differentiation of ASD cases from controls. Cumulatively, our study supports dysregulation of Treg-related lncRNAs in patients with ASD and suggests these lncRNAs as proper peripheral markers for ASD.